Magnetic chitosan polyelectrolyte brush and preparation method and application thereof
Through microfluidic control technology and photo-induced polymerization method, the preparation method of magnetic chitosan polyelectrolyte brushes is improved, and the problems of low preparation efficiency and poor magnetic responsiveness in the prior art are solved, and more efficient graft polymer chains and more uniform particle size are achieved, which are suitable for wastewater treatment and other fields.
Patent Information
- Application Number
- CN202411899529.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing preparation methods for magnetic chitosan polyelectrolyte brushes have problems such as low preparation efficiency, single polyelectrolyte chain, few target functional groups, uneven material particle size, and poor magnetic responsiveness.
Microfluidic control technology was used to add magnetic chitosan solution dropwise to prepare magnetic chitosan particles by one-step method, and graft polymer chains were carried out through methacrylic anhydride modification and photo-induced polymerization to improve grafting efficiency and density.
The magnetic responsiveness and particle size uniformity of magnetic chitosan particles are improved, the grafting efficiency and density of polyelectrolyte chains are enhanced, and it is suitable for wastewater treatment and other fields.
Smart Images

Figure CN119684522A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional polymer materials, and in particular relates to a magnetic chitosan polyelectrolyte brush and a preparation method and application thereof. Background Art
[0002] Nanopolyelectrolytes are widely used in protein adsorption, heavy metal adsorption, water treatment and other fields due to their surface charge, but they are difficult to recycle and have high costs; nanomagnetic adsorbents have a large specific surface area, their magnetic core can be quickly separated by a magnetic field, and their outer layer can adsorb heavy metal ions and dyes through electrostatic effects, but they have stability problems, high preparation costs, limited regeneration efficiency, and selectivity for specific pollutants.
[0003] Magnetic chitosan polyelectrolyte brush is a special polymer structure formed by combining charged polymer chains (polyelectrolyte brushes) with magnetic chitosan. This material usually has a core-shell structure, in which the core part is composed of magnetic materials (such as ferrite, etc.) and the shell part is composed of chitosan and its modified polyelectrolyte brushes. Chitosan chains carry a large number of active groups (such as amino groups, hydroxyl groups, etc.), which can further combine with polyelectrolyte chains to form a brush-like structure; since the material contains magnetic components, the magnetic chitosan polyelectrolyte brush has magnetic responsiveness and can be manipulated and separated by an external magnetic field; the polyelectrolyte brush part is responsive to specific external environmental conditions (such as pH value, ionic strength, temperature, etc.) and can change its conformation and surface properties; chitosan is a natural polymer with good biocompatibility and biodegradability, so the magnetic chitosan polyelectrolyte brush has potential application value in the biomedical field; since the chitosan chain carries a large number of active groups and the polyelectrolyte brush structure can increase the specific surface area and adsorption sites of the material, the magnetic chitosan polyelectrolyte brush exhibits excellent performance in the fields of adsorption and separation.
[0004] The existing method for preparing magnetic chitosan polyelectrolyte brushes is mainly to modify the surface of the magnetic core by chemical methods to form a chitosan layer, and then use physical adsorption or chemical modification methods to graft charged polymer chains on the surface of the chitosan layer to form a polyelectrolyte brush structure. The magnetic chitosan polyelectrolyte brush material prepared by this method has uneven particle size and poor magnetic responsiveness. In addition, the grafting reaction efficiency during the preparation process is low, and only a single polyelectrolyte chain can be grafted, with fewer target functional groups. Summary of the invention
[0005] In view of the shortcomings of the current preparation methods of magnetic chitosan polyelectrolyte brushes, the purpose of the present invention is to provide a magnetic chitosan polyelectrolyte brush and a preparation method and application thereof, so as to solve the problems of low preparation efficiency, single polyelectrolyte chain that can be grafted, few target functional groups, and uneven particle size of the prepared magnetic chitosan polyelectrolyte brush material and poor magnetic responsiveness of the existing preparation methods.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention is to provide a method for preparing a magnetic chitosan polyelectrolyte brush, comprising the following steps:
[0008] S1. Preparation of magnetic chitosan particles: According to the molar ratio of Fe 2+ :Fe 3+ =1:1-2 Take divalent and trivalent iron salts and fully dissolve them in deionized water to obtain a first solution; add the first solution dropwise into the alkaline chitosan solution to obtain magnetic chitosan particles in one step;
[0009] S2. Modification of magnetic chitosan particles: surface modification of the magnetic chitosan particles was performed using methacrylic anhydride to obtain methacrylated magnetic chitosan particles;
[0010] S3 initiation reaction: grafting a photoinitiator HMEM on the surface of the methacrylated magnetic chitosan particles under a nitrogen atmosphere to obtain magnetic chitosan particles with a photoinitiator HMEM on the surface;
[0011] S4. Graft polymerization reaction: The magnetic chitosan particles with the photoinitiator HMEM on the surface are mixed with functional monomers. Under anaerobic and ultraviolet light conditions, the functional monomers are grafted on the surface of the magnetic chitosan particles to form a slender molecular chain structure, thereby preparing a magnetic chitosan polyelectrolyte brush.
[0012] Further, in step S1, the molar ratio of the divalent iron salt to the trivalent iron salt is Fe 2+ :Fe 3+ =1:1.5.
[0013] When the molar ratio of ferrous iron to ferric iron is Fe 2+ :Fe 3+ When the ratio of Mg to ZnO2 is 1:1.5, the particle size uniformity of the prepared magnetic chitosan particles is the best and the magnetic responsiveness is the best.
[0014] Furthermore, the preparation of the magnetic chitosan particles in step S1 specifically comprises the following steps:
[0015] S11. According to the molar ratio of FeCl 2 :FeCl 3=1:1-2 Weigh ferric chloride and ferrous chloride, and fully dissolve them in deionized water to obtain a first solution;
[0016] S12. Weigh a certain amount of chitosan and add it to deionized water, stir and disperse it thoroughly, and adjust the pH of the chitosan solution to 10 to 13 using sodium hydroxide to obtain an alkaline chitosan solution;
[0017] S13. The first solution is placed in a syringe pump, propelled by the syringe pump, and added dropwise to the alkaline chitosan solution after being fully mixed by a vortex mixer. The alkaline chitosan solution is stirred during the addition. After the addition is completed, the stirring reaction is continued for 1 to 2 hours; wherein the stirring speed is: 800 to 1200 r / min;
[0018] S14. After the reaction is completed, the magnetic chitosan particles are obtained by multiple water washing and external magnetic field purification.
[0019] Furthermore, in step S2, the preparation of the methacrylated magnetic chitosan particles specifically comprises the following steps:
[0020] S21. The magnetic chitosan particles and the carbonate-sodium bicarbonate buffer solution are mixed and stirred to dissolve, and the pH is adjusted to 8 to 10 to obtain a second solution;
[0021] S22. Add a certain amount of methacrylic anhydride to the second solution and react at 50 to 55° C. in the dark for 1.5 to 2.5 hours;
[0022] S23. After the light-protected reaction is completed, the product obtained in step S22 is washed with water for multiple times and then collected by an external magnetic field to obtain the methacrylated magnetic chitosan particles.
[0023] Furthermore, the structural formula of the methacrylic anhydride is:
[0024]
[0025] Furthermore, in step S3, the preparation of the magnetic chitosan particles with a photoinitiator HMEM on the surface specifically comprises the following steps:
[0026] S31. Take the methacrylated magnetic chitosan particles, add a small amount of potassium persulfate, and dissolve in deionized water to obtain a third solution;
[0027] S32. In a nitrogen atmosphere, 70-90°C, the photoinitiator HMEM is slowly added to the third solution at a rate of 2 to 3 drops per second through a syringe injection, and the reaction is protected from light for 1.5 to 2.5 hours;
[0028] S33. After the light-shielding reaction is completed, the product obtained in step S32 is washed with water for multiple times and then collected by an external magnetic field to obtain the magnetic chitosan particles with the photoinitiator HMEM on the surface.
[0029] Further, the photoinitiator HMEM is 2-[p-(2-hydroxy-2-methylpropiophenone)]-ethylene glycol-methacrylate (HMEM); the structural formula of the photoinitiator HMEM is:
[0030]
[0031] Furthermore, the photoinitiator HMEM is synthesized by using 2-hydroxy-4'-[-(2-hydroxyethoxy)-2-methylpropiophenone (HMP) as a raw material, and introducing a terminal double bond by using its hydroxyl group and methacryloyl chloride (MC) through Schotten-Baumann reaction.
[0032] Furthermore, in step S4, the preparation of the magnetic chitosan polyelectrolyte brush specifically comprises the following steps:
[0033] S41. The magnetic chitosan particles with a photoinitiator HMEM on the surface are mixed with functional monomers and then nitrogen is used as a protective gas to carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 1.5 to 2.5 hours to prepare a magnetic chitosan polyelectrolyte brush;
[0034] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified magnetic chitosan polyelectrolyte brush.
[0035] Furthermore, in step S41, the mass ratio of the functional monomer to the magnetic chitosan particles with a photoinitiator HMEM on the surface is (1-10):1.
[0036] Furthermore, in step S41, the mass ratio of the functional monomer to the magnetic chitosan particles with a photoinitiator HMEM on the surface is 3:1.
[0037] When the mass ratio of the functional monomer to the magnetic chitosan particles with the photoinitiator HMEM on the surface is 3:1, the particle size uniformity of the prepared magnetic chitosan polyelectrolyte brush is the best.
[0038] Furthermore, the functional monomer is methacryloyloxyethyltrimethylammonium chloride (DMC), acrylic acid (AA), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), sodium p-styrenesulfonate (SS), 2-aminoethyl ester hydrochloride (AMA) or [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide (SBMA).
[0039] The second aspect of the present invention is to provide a magnetic chitosan polyelectrolyte brush prepared according to the above preparation method.
[0040] The third aspect of the present invention is to provide an application of a magnetic chitosan polyelectrolyte brush in the field of wastewater treatment. The magnetic chitosan polyelectrolyte brush is the magnetic chitosan polyelectrolyte brush described above or is prepared by the above preparation method.
[0041] Compared with the prior art, the present invention has at least the following beneficial effects:
[0042] 1. The preparation method of the magnetic chitosan polyelectrolyte brush of the present invention adopts microfluidic technology (adopting a syringe pump to propel, adding dropwise to the magnetic chitosan solution after being fully mixed by a vortex mixer, and being able to fully control the proportion and addition speed of the mixed solution) combined with a one-step method to prepare magnetic chitosan particles, the prepared magnetic chitosan particles have better magnetic responsiveness, and the obtained magnetic chitosan particles have a more uniform particle size. In addition, the magnetic chitosan particles are modified with methacrylic anhydride (MA) and then grafted with a photoinitiator HMEM, which can provide more grafting sites for subsequent grafted polymer chains, thereby improving the grafting efficiency and grafting density of subsequent grafted polymer chains.
[0043] 2. Compared with the traditional method of grafting polymer chains, the preparation method of the magnetic chitosan polyelectrolyte brush of the present invention adopts the photoinitiated polymerization method to prepare the magnetic chitosan polyelectrolyte brush. While grafting more abundant charged functional groups, it greatly improves the reaction efficiency and has good repeatability, and has a broader application prospect in the field of water treatment.
[0044] 3. The present invention adopts a photo-initiated polymerization method to prepare a magnetic chitosan polyelectrolyte brush by surface grafting. The surface grafting density is high, and the grafting density can be regulated by the amount of photoinitiator added. The brush layer thickness of the magnetic chitosan polyelectrolyte brush can be adjusted by changing the monomer amount, reaction time, ionic strength and pH value.
[0045] 4. The present invention prepares magnetic chitosan polyelectrolyte brushes by photoinitiated polymerization. By controlling the feed mass ratio (grafted monomer: magnetic chitosan nanoparticles) and the polymerization reaction time, the polyelectrolyte chain length of the prepared magnetic chitosan polyelectrolyte brushes can be effectively controlled. In addition, no toxic substances that are difficult to remove are introduced during the preparation process. The brushes have good biocompatibility, which makes them have broad application prospects in biomedical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a flow chart for preparing the magnetic chitosan polyelectrolyte brush according to Example 2 of the present invention.
[0047] Figure 2The infrared spectra of the magnetic chitosan particles (CS-MNP) and the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) prepared in Example 1 of the present invention are shown.
[0048] Figure 3 This is a dynamic hysteresis loop diagram of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) prepared in Example 1 of the present invention.
[0049] Figure 4 The electron microscope and physical pictures of the magnetic chitosan particles (CS-MNP) and cationic magnetic chitosan polyelectrolyte brushes (MSPB-DMC) prepared in Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0050] The present invention will be further described below by specific embodiments in conjunction with the accompanying drawings. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0051] The preparation method of the magnetic chitosan polyelectrolyte brush of the invention comprises the following steps: dissolving divalent and trivalent iron salts in deionized water, and then adding the salts dropwise into an alkaline chitosan solution by adopting a microfluidic technology to obtain magnetic chitosan particles in one step; modifying the surface of the magnetic chitosan particles by using methacrylic anhydride (MA), and then grafting a self-made photoinitiator 2-[p-(2-hydroxy-2-methylpropiophenone)]-ethylene glycol-methacrylate (HMEM) in a laboratory; and finally grafting different functional monomers by adopting a photoinitiated polymerization reaction under ultraviolet light irradiation: methacryloyloxyethyltrimethylammonium chloride (DMC), acrylic acid (AA), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), sodium p-styrenesulfonate (SS), 2-aminoethyl ester hydrochloride (AMA), [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide (SBMA), etc., to obtain the magnetic chitosan polyelectrolyte brush.
[0052] The light removal initiator 2-[p-(2-hydroxy-2-methylpropiophenone)]-ethylene glycol-methacrylate (HMEM) used in the present invention is a commercially available drug.
[0053] The structural formula of methacrylic anhydride is:
[0054]
[0055] The preparation method of the photoinitiator (HMEM) is as follows: using 2-hydroxy-4'-[-(2-hydroxyethoxy)-2-methylpropiophenone (HMP) as a raw material, utilizing its hydroxyl group and methacryloyl chloride (MC) to introduce a terminal double bond through a Schotten-Baumann reaction, and synthesizing the photoinitiator 2-[p-(2-hydroxy-2-methylpropiophenone)]-ethylene glycol-methacrylate (HMEM).
[0056] The structural formula of the photoinitiator (HMEM) is:
[0057]
[0058] The chain length of the magnetic chitosan polyelectrolyte brush in the present invention = (D 磁性壳聚糖聚电解质刷 -D 磁性壳聚糖粒子 ) / 2
[0059] Example 1
[0060] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) of this embodiment comprises the following steps:
[0061] 1. Preparation of magnetic chitosan particles:
[0062] S11. Weigh 0.2 mol of ferric chloride and 0.3 mol of ferrous chloride, dissolve them in 50 ml of deionized water to obtain a first solution;
[0063] S12. 2 g of chitosan and 300 ml of deionized water were placed in a three-necked flask, dispersed with high-speed stirring, and the pH of the chitosan solution was adjusted to 12 using sodium hydroxide to obtain an alkaline chitosan solution;
[0064] S13. The first solution is placed in a syringe pump, propelled by the syringe pump, and added dropwise to the alkaline chitosan solution after being fully mixed by a vortex mixer. The alkaline chitosan solution is stirred during the addition. After the addition is completed, the stirring reaction is continued for 1h; wherein the stirring speed is: 800r / min;
[0065] S14. After the reaction is completed, the magnetic chitosan particles are obtained by multiple water washing and external magnetic field purification.
[0066] 2. Modification of magnetic chitosan particles:
[0067] S21. Take 1 g of the magnetic chitosan particles obtained in step S14, dissolve them in 100 ml of 1 M carbonate-sodium bicarbonate buffer, mix and stir to dissolve, and adjust the pH to 9 to obtain a second solution;
[0068] S22. Add 1.17 ml of methacrylic anhydride to the second solution and react at 50-55° C. in the dark for 2 h;
[0069] S23. After the light-protected reaction is completed, the product obtained in step S22 is washed with water for multiple times and then collected by an external magnetic field to obtain methacrylated magnetic chitosan particles.
[0070] 3. Triggering reaction:
[0071] S31. Take 0.5 g of the methacrylated magnetic chitosan particles obtained in step S23, 10 mg of potassium persulfate and 100 ml of deionized water and fully dissolve to obtain a third solution;
[0072] S32. The third solution was placed in a three-necked flask, and after nitrogen was pumped in 5 times, it was placed in a 75°C oil bath and stirred. 0.5 g of the photoinitiator HMEM was slowly added to the third solution using a syringe (at a rate of 2 to 3 drops / s), and the reaction was protected from light for 1.5 h.
[0073] S33. After the light-shielding reaction is completed, the product obtained in step S32 is washed with water for multiple times and then collected by an external magnetic field to obtain the magnetic chitosan particles with the photoinitiator HMEM on the surface.
[0074] 4. Graft polymerization reaction:
[0075] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 1.5 g of methacryloyloxyethyl trimethylammonium chloride (DMC), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 hours to prepare a cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC);
[0076] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC). The chain length of the obtained magnetic chitosan polyelectrolyte brush is 213 nm.
[0077] The magnetic chitosan particles obtained in step S14 and the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) obtained in step S42 were characterized by infrared spectroscopy. Figure 2 As shown, from Figure 2 It can be seen that the prepared magnetic chitosan nanoparticles and cationic magnetic chitosan polyelectrolyte brushes (MSPB-DMC) both detected the characteristic peak of chitosan at 1637 cm -1 , 3308cm -1 , 601cm -1 The characteristic peak of magnetic nanoparticles, 893 cm -1It is the characteristic peak of functional monomer DMC, which proves the successful grafting of DMC.
[0078] The cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) obtained in step S42 was characterized by VSM, and the dynamic hysteresis loop diagram is as follows: Figure 3 As shown, from Figure 3 It can be seen that the saturation magnetic response intensity of the magnetic chitosan polyelectrolyte brush is 18.12emu / g, the magnetic responsiveness is strong, and it can be quickly adsorbed by external magnetism.
[0079] The magnetic chitosan particles (CS-MNP) obtained in step S14 and the cationic magnetic chitosan polyelectrolyte brushes (MSPB-DMC) obtained in step S42 were characterized by SEM and TEM. Figure 4 As shown, Figure 4 The left figure is an electron microscope image and a physical image of the magnetic chitosan particles (CS-MNP) obtained in step S14; the right figure is an electron microscope image and a physical image of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) obtained in step S42; Figure 4 It can be seen that the prepared magnetic chitosan particles (CS-MNP) and magnetic chitosan polyelectrolyte brushes (MSPB-DMC) are granular and have a relatively uniform particle size.
[0080] Example 2
[0081] Preparation of cationic magnetic chitosan polyelectrolyte brush (MSPB-AMPS) in this example (see Figure 1 ), compared with Example 1, the difference of this embodiment is that the functional monomers used in the graft polymerization reaction are different, specifically:
[0082] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 1.5 g of 2-acrylamide-2-methylpropane sulfonic acid (AMPS), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 hours to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-AMPS;
[0083] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-AMPS. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 197 nm.
[0084] Example 3
[0085] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-AA) in this embodiment is different from that in Example 1 in that the functional monomers used in the graft polymerization reaction are different, specifically:
[0086] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 1.5 g of acrylic acid (AA), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 h to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-AA;
[0087] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-AA. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 155 nm.
[0088] Example 4
[0089] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-SS) in this embodiment is different from that in Example 1 in that the functional monomers used in the graft polymerization reaction are different, specifically:
[0090] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 1.5 g of sodium p-styrene sulfonate (SS), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 h to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-SS;
[0091] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-SS. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 98 nm.
[0092] Example 5
[0093] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-AMA) in this embodiment is different from that in Example 1 in that the functional monomers used in the graft polymerization reaction are different, specifically:
[0094] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 1.5 g of 2-aminoethyl ester hydrochloride (AMA), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 hours to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-AMA;
[0095] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-AMA. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 66 nm.
[0096] Example 6
[0097] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-SBMA) in this embodiment is different from that in Example 1 in that the functional monomers used in the graft polymerization reaction are different, specifically:
[0098] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 0.5 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide (SBMA), mix and add to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 hours to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-SBMA;
[0099] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-SBMA. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 134 nm.
[0100] Example 7
[0101] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) of this embodiment is different from that of Example 1 in that the mass ratio of the functional monomer used in the graft polymerization reaction to the magnetic chitosan nanoparticles is 1:1, specifically:
[0102] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 0.5 g of methacryloyloxyethyl trimethylammonium chloride (DMC), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 hours to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-DMC;
[0103] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-DMC. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 15 nm.
[0104] Example 8
[0105] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) of this embodiment is different from that of Example 1 in that the mass ratio of the functional monomer used in the graft polymerization reaction to the magnetic chitosan nanoparticles is different from that of Example 1, which is 2:1. Specifically,
[0106] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 1 g of methacryloyloxyethyl trimethylammonium chloride (DMC), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 h to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-DMC;
[0107] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-DMC. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 146 nm.
[0108] Example 9
[0109] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) of this embodiment is different from that of Example 1 in that the mass ratio of the functional monomer used in the graft polymerization reaction to the magnetic chitosan nanoparticles is 4:1, specifically:
[0110] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 2 g of methacryloyloxyethyl trimethylammonium chloride (DMC), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 h to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-DMC;
[0111] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-DMC. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 322 nm.
[0112] Example 10
[0113] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) of this embodiment is different from that of Example 1 in that the mass ratio of the functional monomer used in the graft polymerization reaction to the magnetic chitosan nanoparticles is 7:1, specifically:
[0114] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 3.5 g of methacryloyloxyethyl trimethylammonium chloride (DMC), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 hours to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-DMC;
[0115] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-DMC. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 550 nm.
[0116] Embodiment 11
[0117] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) of this embodiment is different from that of Example 1 in that the mass ratio of the functional monomer used in the graft polymerization reaction to the magnetic chitosan nanoparticles is 10:1, specifically:
[0118] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 5 g of methacryloyloxyethyl trimethylammonium chloride (DMC), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 2 hours to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-DMC;
[0119] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-DMC. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 631 nm.
[0120] Example 12
[0121] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) in this embodiment is different from that in Example 1 in that the time of the graft polymerization reaction is different, specifically:
[0122] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 1.5 g of methacryloyloxyethyl trimethylammonium chloride (DMC), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 0.5 h to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-DMC;
[0123] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-DMC. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 64.8 nm.
[0124] Example 13
[0125] The preparation of the cationic magnetic chitosan polyelectrolyte brush (MSPB-DMC) in this embodiment is different from that in Example 1 in that the time of the graft polymerization reaction is different, specifically:
[0126] S41. Weigh 0.5 g of the magnetic chitosan particles with a photoinitiator HMEM on the surface obtained in step S33 and 1.5 g of methacryloyloxyethyl trimethylammonium chloride (DMC), mix them and add them to a photoreactor, use nitrogen as a protective gas, and carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 1 hour to prepare a cationic magnetic chitosan polyelectrolyte brush MSPB-DMC;
[0127] S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified cationic magnetic chitosan polyelectrolyte brush MSPB-DMC. The chain length of the obtained magnetic chitosan polyelectrolyte brush is 165.1 nm.
[0128] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a magnetic chitosan polyelectrolyte brush, characterized in that: The following steps are involved: S1. Preparation of magnetic chitosan particles: According to the molar ratio of Fe 2+ :Fe 3+ =1:1-2 Take divalent and trivalent iron salts and fully dissolve them in deionized water to obtain a first solution; add the first solution dropwise into the alkaline chitosan solution to obtain magnetic chitosan particles in one step; S2. Modification of magnetic chitosan particles: surface modification of the magnetic chitosan particles was performed using methacrylic anhydride to obtain methacrylated magnetic chitosan particles; S3 initiation reaction: grafting a photoinitiator HMEM on the surface of the methacrylated magnetic chitosan particles under a nitrogen atmosphere to obtain magnetic chitosan particles with a photoinitiator HMEM on the surface; S4. Graft polymerization reaction: The magnetic chitosan particles with the photoinitiator HMEM on the surface are mixed with functional monomers, and under anaerobic and ultraviolet light irradiation conditions, the functional monomers are grafted on the surface of the magnetic chitosan particles to form a slender molecular chain structure to prepare a magnetic chitosan polyelectrolyte brush, wherein the photoinitiator HMEM is 2-[p-(2-hydroxy-2-methylpropiophenone)]-ethylene glycol-methacrylate (HMEM).
2. The method for preparing a magnetic chitosan polyelectrolyte brush according to claim 1, characterized in that: In step S1, the molar ratio of the divalent iron salt to the trivalent iron salt is Fe 2+ :Fe 3+ =1:1.
5.
3. The method for preparing the magnetic chitosan polyelectrolyte brush according to claim 1, characterized in that: The preparation of the magnetic chitosan particles in step S1 specifically comprises the following steps: S11. Weigh ferric chloride and ferrous chloride according to a molar ratio of FeCl2:FeCl3 = 1:1 to 2, and fully dissolve them in deionized water to obtain a first solution; S12. Weigh a certain amount of chitosan and add it to deionized water, stir and disperse it thoroughly, and adjust the pH of the chitosan solution to 10 to 13 using sodium hydroxide to obtain an alkaline chitosan solution; S13. The first solution is placed in a syringe pump, propelled by the syringe pump, and added dropwise to the alkaline chitosan solution after being fully mixed by a vortex mixer. The alkaline chitosan solution is stirred during the addition. After the addition is completed, the stirring reaction is continued for 1 to 2 hours; wherein the stirring speed is: 800 to 1200 r / min; S14. After the reaction is completed, the magnetic chitosan particles are obtained by multiple water washing and external magnetic field purification.
4. The method for preparing the magnetic chitosan polyelectrolyte brush according to claim 1, characterized in that: In step S2, the preparation of the methacrylated magnetic chitosan particles specifically comprises the following steps: S21. The magnetic chitosan particles and the carbonate-sodium bicarbonate buffer solution are mixed and stirred to dissolve, and the pH is adjusted to 8 to 10 to obtain a second solution; S22. Add a certain amount of methacrylic anhydride to the second solution and react at 50 to 55° C. in the dark for 1.5 to 2.5 hours; S23. After the light-protected reaction is completed, the product obtained in step S22 is washed with water for multiple times and then collected by an external magnetic field to obtain the methacrylated magnetic chitosan particles.
5. The method for preparing the magnetic chitosan polyelectrolyte brush according to claim 1, characterized in that: In step S3, the preparation of the magnetic chitosan particles with a photoinitiator HMEM on the surface specifically comprises the following steps: S31. Take the methacrylated magnetic chitosan particles, add a small amount of potassium persulfate, and dissolve in deionized water to obtain a third solution; S32. In a nitrogen atmosphere, 70-90°C, the photoinitiator HMEM is slowly added to the third solution at a rate of 2 to 3 drops per second through a syringe injection, and the reaction is protected from light for 1.5 to 2.5 hours; S33. After the light-shielding reaction is completed, the product obtained in step S32 is washed with water for multiple times and then collected by an external magnetic field to obtain the magnetic chitosan particles with the photoinitiator HMEM on the surface.
6. The method for preparing the magnetic chitosan polyelectrolyte brush according to claim 1, characterized in that: In step S4, the preparation of the magnetic chitosan polyelectrolyte brush specifically comprises the following steps: S41. The magnetic chitosan particles with a photoinitiator HMEM on the surface are mixed with functional monomers and then nitrogen is used as a protective gas to carry out a graft polymerization reaction under ultraviolet light. The functional monomers are grafted on the surface of the magnetic chitosan particles to form an elongated molecular chain structure. The reaction is carried out for 1.5 to 2.5 hours to prepare a magnetic chitosan polyelectrolyte brush; S42. The product obtained in step S41 is washed with water for multiple times and then collected by an external magnetic field to obtain a purified magnetic chitosan polyelectrolyte brush.
7. The method for preparing the magnetic chitosan polyelectrolyte brush according to claim 6, characterized in that: In step S41, the mass ratio of the functional monomer to the magnetic chitosan particles with a photoinitiator HMEM on the surface is (1-10):
1.
8. The method for preparing the magnetic chitosan polyelectrolyte brush according to claim 1, characterized in that: The functional monomer is methacryloyloxyethyltrimethylammonium chloride (DMC), acrylic acid (AA), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), sodium p-styrenesulfonate (SS), 2-aminoethyl ester hydrochloride (AMA) or [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide (SBMA).
9. A magnetic chitosan polyelectrolyte brush, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
10. Application of a magnetic chitosan polyelectrolyte brush in the field of wastewater treatment, characterized in that: The magnetic chitosan polyelectrolyte brush is the magnetic chitosan polyelectrolyte brush according to claim 9 or is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method for chitosan modified algae removal flocculant
CN108314759A
Method for continuously preparing photoinitiator by microreactor
CN114272873A
Preparation method of water-soluble polymer with branched structure
CN114656603A
Modified chitosan-based magnetic flocculant as well as preparation method and application thereof
CN115340157A
Method for preparing gelatin polyelectrolyte brush by photo-initiation emulsion polymerization method
CN117487095A